Neighborhood disadvantage, greenness and population density as predictors of breastfeeding practices: a population cohort study from Finland - Galante Laura; Lahdenperä Mirkka; Rautava Samuli; Pentti Jaana; Ollila Helena; Tarro Saija; Vahtera Jussi; Gonzales Inca Carlos; Kivimäki Mika; Lummaa Virpi; Lagström Hanna (Oxford University Press, 2025)
Background
Many environmental factors are known to hinder breastfeeding, yet the role of the family living environment in this regard is still poorly understood.
Objectives
Therefore, we used data from a large cohort to identify associations between neighborhood characteristics and breastfeeding behavior.
Methods
Our observational study included 11,038 children (0-2 years) from the Southwest Finland Birth Cohort. Participant information were obtained from the Medical Birth Register and municipal follow-up clinics. Neighborhood socioeconomic disadvantage, greenness and population density were measured for a period of 5 years prior to childbirth within the residential neighborhood on a 250×250m grid. Any breastfeeding and breastfeeding at six months were the primary outcomes. Binary logistic regression models were adjusted for maternal health and socioeconomic factors.
Results
Adjusted analyses suggest that mothers living in less populated areas were less likely to display any breastfeeding (OR: 0.46; 95% CI 0.36, 0.59) and breastfeeding at six months (OR: 0.37; 95% CI: 0.34, 0.40). Mothers living in highly disadvantaged neighborhoods were less likely to display any breastfeeding if the neighborhood was less populated (OR: 0.54, 95% CI: 0.30, 0.95) but more likely to breastfeed at six months if the neighborhood was highly populated (OR: 3.74; 95% CI: 1.92, 7.29). Low greenness was associated with higher likelihood of any breastfeeding (OR: 3.82; 95% CI: 1.53, 9.55) and breastfeeding at six months (OR: 4.41; 95% CI: 3.44, 5).
Conclusions
Our results suggest that neighborhood characteristics is associated with breastfeeding behavior in Finland. Unravelling breastfeeding decisions linked to the living environment may help identify interventions that will allow the appropriate support for all mothers and infants across different environmental challenges.